Medium-low temperature reduction of high-iron Bayer process red mud using biomass pine sawdust - LI Heng; LIU Xiao-ming; ZHAO Xi-bin; CHEN Jiao-long; YIN Hai-feng (工程科学学报)
An experiment was conducted to determine the difference between using biomass pine sawdust and pulverized coal in the reduction roasting of high-iron Bayer process red mud from the perspective of reduction temperature, reduction time, and reducing agent dosage. Experimental results show that biomass pine sawdust reduction roasting is quicker, occurs at a lower temperature, and is a superior process to pulverized coal reduction roasting. The mechanism of using biomass pine sawdust in reduction roasting of high-iron Bayer process red mud at a low temperature was investigated using thermal analysis, X-ray diffraction, and dynamic analysis. In addition, the optimum conditions involved in reducing high-iron Bayer process red mud were determined using biomass pine sawdust at medium and low temperatures. It is found that when using 20% biomass pine sawdust in mass at a reduction temperature of 650℃ and a reduction time of 30 min, the high-iron red mud in the Bayer process can be completely magnetized. A thermogravimetric experiment conducted on biomass pine sawdust indicates that the main stage of sawdust pyrolysis occurs within a temperature range of 250-375℃. The pyrolysis rate reaches a maximum at about 350℃, but tends to be gentle at 450℃. The main stage of pulverized coal pyrolysis occurs at 300-700℃; the pyrolysis rate is at its maximum at 450℃ but it tends to be gentle at 650℃. The kinetic study shows that at a temperature of 300-400℃, the apparent pyrolysis activation energy of the sawdust is much lower than that of pulverized coal, indicating that sawdust is more prone to pyrolysis than pulverized coal at this temperature range. In summary, biomass reduces high-iron Bayer red mud at a lower temperature, which is about 200℃ lower than that of coal-based reduction.